Promising Eco-Friendly Nanoparticles for Managing Bottom Rot Disease in Lettuce (Lactuca sativa var. longifolia) - Nashwa A. H. Fetyan; Tarek A. Essa; Tamer M. Salem; Ahmed Aboueloyoun Taha; Samah Fawzy Elgobashy; Nagwa A. Tharwat; Tamer Elsakhawy (Microbiology Research, 2024)
Developing innovative, eco-friendly fungicide alternatives is crucial to mitigate the substantial threat fungal pathogens pose to crop yields. In this study, we assessed the in vitro effectiveness of SiO2, CuO, and γFe2O3 nanoparticles against Rhizoctonia solani. Furthermore, greenhouse experiments were conducted in artificially infested soil to evaluate the in vivo impact of nanoparticles under study. Two application methods were employed: soil drenching with 10 mL per pot at concentrations of 50, 100, and 200 mg L−1, and seedling dipping in nanoparticle suspensions at each concentration combined with soil drench. The combined treatment of 200 mg L−1 γFe2O3 or CuO nanoparticles showed the highest in vitro antifungal activity. Conversely, SiO2 nanoparticles demonstrated the lowest in vitro activity. Notably, the application of 200 mg/L SiO2 via the dipping and soil drenching methods decreased counts of silicate-solubilizing bacteria and Azospirillum spp. Whereas, application of 100 mg L−1 γFe2O3 nanoparticles via soil drenching increased soil bacterial counts, and CuO nanoparticles at 50 mg L−1 through dipping and soil drenching had the highest dehydrogenase value. γFe2O3 nanoparticles improved plant photosynthetic pigments, reduced malondialdehyde levels, and minimized membrane leakage in lettuce plants. A root anatomical study showed that 200 mg L−1 CuO nanoparticles induced toxicity, whereas 200 mg L−1 γFe2O3 or SiO2 nanoparticles positively affected root diameter, tissue structure, and various anatomical measurements in lettuce roots. γFe2O3 nanoparticles hold promise as a sustainable alternative for managing crop diseases.